Rediseño e implementación de las instalaciones eléctricas para los laboratorios de la carrera de Ingeniería Electromecánica en la Universidad Técnica de Cotopaxi cumpliendo con las normativas regionales vigentes - Chávez Pichucho, Mercy Lorena (2017)
The present investigative work describes the realization of the redesign of the three-phase electrical installations of the laboratories of the Electromechanical Engineering Career, in the Technical University of Cotopaxi, fulfilling current regulations. This project was carried out in order to have three-phase power points that allow the use of the didactic modules that the Electromechanical Engineering Career Laboratory has. In order to execute the redesign, an assessment of the existing facilities was carried out, in order to capture the survey of the single-line diagram, then the load analysis was carried out for the new load centers, once the respective calculations have been determined, and knowing the technical characteristics of the materials is the selection of the elements that comply with current standards, the type of driver, protections and other accessories to be used is chosen. An economic valuation of the required investment is made and the implementation of each of the areas is carried out in compliance with the current regulations.